K(alpha)/K(beta) ratios of fluorescence X-rays as an information source on the depth distribution of iron in a low Z matrix - Trojek, Tomás; Cechák, Tomás; Musílek, Ladislav (Analytical sciences, 2008)
This paper describes how the K(alpha)/K(beta) count rate ratio of the characteristic X-rays of a given element can be applied to determine the depth at which a layer or a grain of that element is located. The theoretical background and a basic description of the K(alpha)/K(beta) technique are given in the introduction. The experimental part of the paper deals with measurements of thick standard pure iron, intermediately thick iron foils, and layers prepared with a powder of Prussian blue. All these specimens were analyzed alone, and they were also analyzed overlaid with a low Z matrix. The light matrix consisted of sheets of paper of known thickness. Paper was chosen, because we take into account the subsequent application of this technique to surveys of historical monuments. The relation between the K(alpha) count rate, the K(alpha)/K(beta) count rate ratio, and the distribution of iron in the paper matrix are presented here.